Bullinger am Kap der Guten Hoffnung? Theologische bemerkungen zum einfluss Bullingers in Südafrika - V. E. d'Assonville (Acta Theologica)
Articles regularly feature the notion of a forceful influence that was exerted by Heinrich Bullinger (sixteenth-century church reformer and successor of Zwingli in Zurich) on the early settlement during the first sixty years since Van Riebeeck’s arrival at the Cape. Various publications conclude by stating Bullinger’s theological influence on the jurisprudence and social structures in the community. The issue as to whether and to what extent Bullinger’s theology and writing played a role in the Cape during the seventeenth and eighteenth centuries and that of dealing with, interpretating and treating historical sources and texts are of historical concern. Furthermore, the importance of discerning between historical and theological texts has theological and historiographical consequences. This article points out that the issue of theological influence during the first half of the history of settlement at the Cape is more complex than it may seem at first glance, on the one hand, and that it is difficult to gauge the importance of Bullinger’s direct or indirect influence during this period, on the other.